Is incidence of multiple HPV genotypes rising in genital infections? - Amir Sohrabi; Masoud Hajia; Firouzeh Jamali; Faranak Kharazi (Elsevier, 2017)
Frequency of cervical cancer related to Human Papilloma Virus (HPV) has increased remarkably in less-developed countries. Hence, applying capable diagnostic methods is urgently needed, as is having a therapeutic strategy as an effective step for cervical cancer prevention. The aim of this study was to investigate the prevalence of various multi-type HPV infection patterns and their possible rising incidence in women with genital infections.This descriptive study was conducted on women who attended referral clinical laboratories in Tehran for genital infections from January 2012 until December 2013. A total of 1387 archival cervical scraping and lesion specimens were collected from referred women. HPV genotyping was performed using approved HPV commercial diagnostic technologies with either INNO-LiPA HPV or Geno Array Test kits.HPV was positive in 563 cases (40.59%) with mean age of 32.35 ± 9.96. Single, multiple HPV genotypes and untypable cases were detected in 398 (70.69%), 160 (28.42%) and 5 (0.89%) cases, respectively. Multiple HPV infections were detected in 92 (57.5%), 42 (26.2%), 17 (10.6%) and 9 (5.7%) cases as two, three, four and five or more genotypes, respectively. The prevalence of 32 HPV genotypes was determined one by one. Seventeen HPV genotypes were identified in 95.78% of all positive infections. Five dominant genotypes, HPV6, 16, 53, 11 and 31, were identified in a total of 52.35%of the HPV positive cases.In the present study, we were able to evaluate the rate of multiple HPV types in genital infections. Nevertheless, it is necessary to evaluate the role of the dominant HPV low-risk types and the new probably high-risk genotypes, such as HPV53, in the increasing incidences of genital infections. Keywords: Multiple HPV Types, Incidence, Genital infection, Cervical cancer, Iran